COMPARATIVE REMOVAL OF METHYLENE BLUE FROM AQUEOUS SOLUTION USING DIFFERENT ADSORBENTS - Marzouk Trifi, Ikhlass; Trifi, Beyram; Zendah, Houda; Hamrouni, Béchir (Journal of the Chilean Chemical Society, 2021)
A comparative study for the adsorption of Methylene blue onto different prepared adsorbents was investigated. First, a comparative study was performed with different parameters between orange peels, orange peels activated with phosphoric acid, orange peels activated encapsulating in alginate and orange peels activated encapsulating in magnetic alginate. It can be concluded that the magnetic alginate composite beads were the best adsorbent. Then the isotherms, kinetics and regeneration studies for the removal of Methylene blue were studied onto magnetic alginate composite beads. The adsorption of Methylene blue on magnetic alginate composite beads was applied to isotherm models showed that the interaction of Methylene blue with magnetic alginate composite beads surface is localized monolayer adsorption. The kinetic process flow a pseudo-second-order kinetic. Finally, the removal efficiencies were maintained using HCl solution as desorbing agent after five cycles of adsorption-desorption.